A randomized study of olanzapine-containing versus standard antiemetic regimens for the prevention of chemotherapy-induced nausea and vomiting in Chinese breast cancer patients. (April 2020) - Yeo, Winnie; Lau, Thomas KH.; Li, Leung; Lai, Kwai Tung; Pang, Elizabeth; Cheung, Maggie; Chan, Vicky TC.; Wong, Ashley; Soo, Winnie MT.; Yeung, Vanessa TY.; Tse, Teresa; Lam, Daisy CM.; et al.
Abstract: Objectives: Chemotherapy-induced nausea and vomiting (CINV) are distressing symptoms. This randomized study evaluated the antiemetic efficacies of standard antiemetic regimen with/without olanzapine. Patients and methods: Eligible patients were chemotherapy-naive Chinese breast cancer patients who were planned for (neo)adjuvant doxorubicin/cyclophosphamide. Antiemetic regimen for all studied population included aprepitant, ondansetron and dexamethasone; patients were randomized to Olanzapine (with olanzapine) or Standard arms (without olanzapine). Patients filled in self-reported diaries and completed visual analogue scales for nausea, as well as Functional Living Index-Emesis questionnaires. Blood profiles including fasting glucose and lipids were monitored. Results: 120 patients were randomized. In Cycle 1 doxorubicin/cyclophosphamide, the Olanzapine arm had significantly higher rates of "Complete Response" than the Standard arm: 65.0% vs 38.3% in the overall period (p = 0.0035), 70.0% vs 51.7% in the acute period (p = 0.0397) and 92.9% vs 74.2% in the delayed period (p = 0.0254). Olanzapine arm also had significantly higher rates of "No significant nausea" and "No nausea" during all 3 time-frames and better QOL. Similar findings were also revealed throughout multiple cycles. Pre-study abnormalities in glucose and lipids occurred in 39.7% and 34.2% of the studied population respectively; there were no differences in these parameters between the two arms at end-of-study assessment. Conclusion: The addition of olanzapine to standard aprepitant-based antiemetic regimen provides clinically meaningful improvement in controlling CINV. This was associated with a positive impact on QOL and tolerable toxicity profiles among Chinese breast cancer patients receiving doxorubicin/cyclophosphamide chemotherapy. Further studies on metabolic profiles of breast cancer patients are warranted. Highlights: Olanzapine is reported to reduce nausea and vomiting after highly emetogenic chemotherapy. Reported studies are limited by heterogeneous populations receiving diverse cytotoxic regimes. This study enrolled Chinese breast cancer patients undergoing doxorubicin/cyclophosphamide. Adding olanzapine to aprepitant/ondansetron/dexamethasone is superior in controlling nausea and vomiting. Baseline investigations shows a surprisingly high rate of glucose and lipids abnormalities.